Mercury flow through an Asian rice-based food web. (October 2017) - Abeysinghe, Kasun S.; Qiu, Guangle; Goodale, Eben; Anderson, Christopher W.N.; Bishop, Kevin; Evers, David C.; Goodale, Morgan W.; Hintelmann, Holger; Liu, Shengjie; Mammides, Christos; Quan, Rui-Chang; Wang, Jin; et al.
Abstract: Mercury (Hg) is a globally-distributed pollutant, toxic to humans and animals. Emissions are particularly high in Asia, and the source of exposure for humans there may also be different from other regions, including rice as well as fish consumption, particularly in contaminated areas. Yet the threats Asian wildlife face in rice-based ecosystems are as yet unclear. We sought to understand how Hg flows through rice-based food webs in historic mining and non-mining regions of Guizhou, China. We measured total Hg (THg) and methylmercury (MeHg) in soil, rice, 38 animal species (27 for MeHg) spanning multiple trophic levels, and examined the relationship between stable isotopes and Hg concentrations. Our results confirm biomagnification of THg/MeHg, with a high trophic magnification slope. Invertivorous songbirds had concentrations of THg in their feathers that were 15x and 3x the concentration reported to significantly impair reproduction, at mining and non-mining sites, respectively. High concentrations in specialist rice consumers and in granivorous birds, the later as high as in piscivorous birds, suggest rice is a primary source of exposure. Spiders had the highest THg concentrations among invertebrates and may represent a vector through which Hg is passed to vertebrates, especially songbirds. Our findings suggest there could be significant population level health effects and consequent biodiversity loss in sensitive ecosystems, like agricultural wetlands, across Asia, and invertivorous songbirds would be good subjects for further studies investigating this possibility. Graphical abstract: Highlights: Hg concentrations were measured across rice-based food webs in Guizhou, China. Of 38 animal species, THg concentrations were highest for invertivorous songbirds. High THg levels in rice pests and in granivorous birds suggest rice as a source. Levels of THg in songbird feathers at mining site were among highest ever recorded. Even at non-mining site, THg in such feathers were 3X threshold of adverse effects. Abstract : THg concentrations in rice-based food webs in mining and non-mining sites of Guizhou Province, China are highest in the feathers of invertivorous birds, with levels even at the non-mining site 3X the threshold for adverse effects.